De l'Atlantique à l'océan Virtuel : expériences maliennes (itinéraires des enseignants à travers les TIC) - Toure, Kathryn; Cissé, Daouda Dougoumalé; Cherrier-Daffé, Catherine (Langaa RPCIG, 2015)
Teachers, through their pedagogical appropriation of information and communication technology (ICT) are sometimes bewildered -- as if in the middle of a new ocean. Behind them is all they have learned, and before them lies so much they do not know and that invites exploration. They accompany their students and invite others to join them in this journey. They do their best to learn, deepen their teaching, and perhaps also, through their example and their actions, encourage the revitalization of the school system. Internet is like a sea of knowledge, in a changing world, where one has to navigate with great enthusiasm, curiosity and skill, as well as patience, impatience and perseverance. Let the experiences of Malian teachers shared in this book inspire you.
Keywords: Education -- Information technology -- Mali -- Case studies.; Computer-assisted instruction -- Mali -- Case studies.; Educational technology -- Mali -- Case studies.; Enseignement assisté par ordinateur -- Mali -- Études de cas.; Technologie éducative -- Mali -- Études de cas.; African history.; EDUCATION / Computers & Technology.; Computer-assisted instruction; Educational technology; Mali; Education; Case studies